1958
DOI: 10.1107/s0365110x58001663
|View full text |Cite
|
Sign up to set email alerts
|

Studies of some carbon compounds of the transition metals. I. The crystal structure of dicyclopentadienyldiiron tetracarbonyl

Abstract: Dicyclopentadienyldi-iron tetracarbonyl, Fe2(CO)4(C5:Hs)2, is monoclinic with a = 7-07-4-0.03, b = 12.46~=0.05, c = 7.99+0.04 A, fl = 108 ° 25'±25', Z = 2 and space group t)21/c. The structure has been determined from two-dimensional data estimated visually from Weissenberg photographs taken with Co Ka radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

1959
1959
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(42 citation statements)
references
References 4 publications
3
38
0
1
Order By: Relevance
“…À ion derivatives of 1-4 by salt-elimination strategies failed and gave the known dimeric complex [27] as the sole identifiable decomposition product. Reasoning that in the context of tripodal triamido uranium derivatives the relatively contracted valence orbitals of iron might disfavor uraniummetal bond formation, or that the…”
Section: Resultsmentioning
confidence: 97%
“…À ion derivatives of 1-4 by salt-elimination strategies failed and gave the known dimeric complex [27] as the sole identifiable decomposition product. Reasoning that in the context of tripodal triamido uranium derivatives the relatively contracted valence orbitals of iron might disfavor uraniummetal bond formation, or that the…”
Section: Resultsmentioning
confidence: 97%
“…For the iron systems both cis [12] and trans [13][14][15] isomers of (g 5 -C 5 H 5 ) 2 Fe 2 (CO) 2 (l-CO) 2 formal Fe-Fe single bonds, as well as (g 5 -C 5 H 5 ) 2 Fe 2 (l-CO) 3 with a formal r þ 2 2 p Fe@Fe double bond of triplet spin multiplicity, are stable compounds [16][17][18][19], characterized structurally by X-ray diffraction. Furthermore, (g 5 -C 5 H 5 ) 2 Fe 2 (l-CO) 2 , with a formal Fe"Fe triple bond, is a probable intermediate in the pyrolysis of (g 5 -C 5 H 5 ) 2 Fe 2 (CO) 2 (l-CO) 2 to give the tetrahedral Fe 4 cluster [20] (g 5 -C 5 H 5 ) 4 Fe 4 (l 3 -CO) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray and neutron diffraction studies [7][8][9] showed that I has a centrosymmetric structure in the solid phase with two bridging and two terminal carbonyl groups (trans-bridged form). Low-temperature crystallization made possible isolation of the cis form [10].…”
Section: Experimental Datamentioning
confidence: 99%
“…X-ray study of I together with sublimation experiments and low-temperature crystallization led to conclusion that the cis form is thermodynamically less stable [7,10]. 1 H-NMR spectra of I dissolved in C 6 D 6 -CS 2 showed, however, that the cis-bridged isomer is by 4.2 kJ/mol more stable than the trans one, with the energy barrier of transbridged-I´non-bridged-I interconversion of about 54.3 kJ/mol [18].…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation